Periodontal Outcomes in Anterior Teeth following Presurgical Orthodontic Decompensation in Patients with Skeletal Class III Malocclusion: A Single-Arm Systematic Review and Meta-Analysis - Yun He; Siyuan Wang; Hui Xiong (International Journal of Dentistry)
Objective. This study aims to systematically review and analyze the periodontal outcomes of presurgical orthodontic decompensation (POD) in patients with skeletal Class III malocclusion and to identify the key influencing factors. Material and Methods. We searched the Web of Science, PubMed, Scopus, Embase, and Cochrane Library databases. The outcomes included measurements related to periodontal soft or hard tissues. Results. A total of 3,904 records were found, of which 10 were included. The meta-analysis revealed significant alveolar bone loss in mandibular incisors on both the lingual and labial sides during POD, with a more pronounced loss on the lingual side at the apex level and on the labial side near the crown. The maxillary incisors demonstrated significant bone loss, primarily on the lingual side. No significant bone loss was observed during postsurgical orthodontic treatment. Gingival recession was statistically significant but had a minor clinical impact. Incisor proclination was found to influence the gingival recession. However, no correlation was observed between bone loss and incisor proclination, vertical facial type, or sex. Conclusions. POD for skeletal Class III patients results in alveolar bone loss, particularly on the lingual side at the mandibular incisors’ apex level and labial side at the crown level, and clinically acceptable gingival recession.